The Nexus Between Research and Development, Protection of Intellectual Property Rights and Financial Development. A European Perspectiv - Gheorghe Hurduzeu; Radu Lupu; Iulia Lupu; Adrian Cantemir Calin (Amfiteatru Economic Journal, 2022)
Considering the role of research and development in increasing knowledge with creative work, in this study, we analyse the link between research and development expenditures in several performance sectors (business, government, higher education) and indicators regarding the protection of intellectual property rights and financial development. The analysis refers to the member states of the European Union, divided into two categories (Central and Eastern Europe and Western Europe), for the period 2007-2020. The results obtained after using a panel data methodology suggest that the settings are different for the two groups of countries. This new perspective (i.e., the disparity between regions and the type of sector) can be considered as evidence in favour of decisions to support research and development expenditures in sensitive situations.
Keywords: O30; O34; G10; G20; 330; research and development; intellectual property rights protection; financial development index; panel approach; European Union.